NGHIÊN CỨU PHÂN HỦY MÀU NHUỘM DƯỚI SỰ HỖ TRỢ CỦA SIÊU ÂM - Hà, Bùi Mạnh; Trinh, Bùi Nguyễn Hoàng; Thạch, Lê Ngọc (Vietnam Journal of Science and Technology, 2012)
EFFECTS OF SONICATION ON REMOVAL COLOR SOME REACTIVE DYES Ultrasonic irradiation had been one of the advanced oxidation methods for decolorization four commercial reactive dyes: Sunzol Black B 150% (Reactive black 5), Procion Red MX 5B (Reactive red 2), Remazol Brilliant Blue R (Reactive blue 19), and Sunzol turquoise blue G 133 (Reactive blue 21). The objective of this paper is investigation of the low frequency - high power sonication (750 W-20 KHz) in the dye decolorization (measured by UV absorption) as well as control the experiment conditions by varying irradiation time, dye concentration, pH, temperature, air flow rate. The results indicated that the sonication had strong capacity in the dye decolorization.